Moderasi Pertumbuhan Ekonomi Terhadap Pengaruh Dana Perimbangan Daerah dalam Pengalokasian Belanja Modal pada Pemerintah Provinsi di Indonesia - Melasari; Fitriasuri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study examines the impact of regional equalization funds on provincial government capital expenditure in Indonesia, with economic growth as a moderating variable. The analysis was conducted using secondary data from the APBD realization reports and the Central Statistics Agency for the period 2018-2022. The results show that general allocation funds, special allocation funds, and revenue sharing funds have a significant impact on capital expenditure. Economic growth was found to moderate the relationship between revenue sharing funds and capital expenditure, but not for general allocation funds and special allocation funds. These findings provide important insights for optimizing regional fiscal policies to increase revenue and capital expenditure, as well as supporting the equitable distribution of infrastructure development.